2022
DOI: 10.1177/16878132221121056
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics analysis of a gear system considering tooth contact temperature and dynamic wear

Abstract: Increased temperature and surface wear of high-speed and heavy-load gears are inevitable. Thermal deformation and surface wear modify the position of the action line of the tooth surface and thus influence the dynamic characteristics of the gear mesh. In this study, the elastic modulus and tooth profile thermal deformation were calculated when the tooth contact temperature (TCT) increased. A dynamic wear calculation method was used to combine the dynamic mesh force and dynamic wear coefficient caused by the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In order to investigate the real load distribution on the tooth surface, this paper uses gear loaded tooth contact analysis (LTCA) based on the finite element method to calculate the w n distribution. If a meshing cycle (an angular pitch, 2π/z) is equally divided into N instantaneous positions, and M grid nodes along the tooth width direction, then after finite element calculation converges, the normal load on the current contact line at the ith instant meshing position can be obtained as in Equation (11), where the superscript "n" represents the normal direction.…”
Section: Semi-analytical Methods For Solving Tooth Surface Friction F...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the real load distribution on the tooth surface, this paper uses gear loaded tooth contact analysis (LTCA) based on the finite element method to calculate the w n distribution. If a meshing cycle (an angular pitch, 2π/z) is equally divided into N instantaneous positions, and M grid nodes along the tooth width direction, then after finite element calculation converges, the normal load on the current contact line at the ith instant meshing position can be obtained as in Equation (11), where the superscript "n" represents the normal direction.…”
Section: Semi-analytical Methods For Solving Tooth Surface Friction F...mentioning
confidence: 99%
“…Chen et al [10] studied the change in tooth backlash caused by the tooth bulk temperature, which in turn affects the dynamic performance of gear meshing in the shearer. Yuan et al [11] revealed that tooth surface contact temperature and dynamic wear will cause changes in the contact position on the line of action, thereby changing the dynamic characteristics of the gear system. Liu et al [12] developed three drums with different helical angles to investigate improved loading performance and studied the loading performance of the shearer drum.…”
Section: Introductionmentioning
confidence: 99%